La escultura como medio simbolico para la representacion del rol historico de la mujer orense en l asociedad - Lavanda Japa, Elsa Paulette (Machala, 2025)
This research focuses on the importance of the historical role of Orense women in society and the problem of the scarce historical record that has been collected of the women who have made history in this region. Despite their active and fundamental participation in various areas – social, economic, political, cultural – Orense women have historically been made invisible in official narratives, perpetuating an incomplete and biased vision of the past. This research is justified by the need to recognize and make visible the legacy of these women, whose participation has been crucial for the development of the region. The main objective is to analyze the historical role of Orense women in society, identifying and documenting their contributions in different periods and areas. The problem of the scarce historical record of Orense women is due, in part, to the lack of interest and recognition on the part of traditional historiography, which has privileged the male figure as the protagonist of history. This situation has generated an incomplete and biased vision of the past, making the significant contributions of women invisible. This lack of representation not only affects collective memory, but also perpetuates gender stereotypes and limits the recognition of the fundamental role of women in the construction of Orense society. To recover and make visible the legacy of Orense women, a research methodology is proposed that combines the review of documentary sources – archives, books, photographs – with the recovery of oral testimonies – interviews with Orense women and their descendants. Additionally, the creation of a metal sculptural artistic work is proposed that serves as a tribute and recognition to these women, disseminating their legacy in a creative and accessible way. The sculptural work referring to women made of metal is conceived as an artistic piece that dialogues with historical research, symbolically representing the strength, resilience and legacy of the women of Orense. Through its form, texture and materials, the sculpture seeks to transmit the presence and importance of these women in the history of the region. This work is composed of eight pieces of metal, which have different sizes that when put together form a face, this will give the illusion of the faces of women who have made history and there is no information about them, in the same way on the base board where the piece will be anchored they will have different historical contexts attached but these will start out large, visible until little by little these same contexts decrease, becoming smaller and smaller, implying that this is how this topic is seen in the eyes of society since it can be deduced that most people are not aware of this critical situation that generates an information spasm in the province of Oro. It is hoped that this work will become a space for meeting and reflection, inviting the community to recognize and value the contribution of women in the construction of their society.
La presente investigación se centra en la importancia del rol histórico de la mujer orense en la sociedad y la problemática del escaso registro histórico que se ha recogido de las mujeres que han hecho historia en esta región. A pesar de su participación activa y fundamental en diversos ámbitos –social, económico, político, cultural–, las mujeres orenses han sido históricamente invisibilizadas en los relatos oficiales, perpetuando una visión incompleta y sesgada del pasado. Esta investigación se justifica por la necesidad de reconocer y visibilizar el legado de estas mujeres, cuya participación ha sido crucial para el desarrollo de la región. Se plantea como objetivo principal analizar el rol histórico de la mujer orense en la sociedad, identificando y documentando sus aportes en diferentes períodos y ámbitos. La problemática del escaso registro histórico de las mujeres orenses se debe, en parte, a la falta de interés y reconocimiento por parte de la historiografía tradicional, que ha privilegiado la figura masculina como protagonista de la historia. Esta situación ha generado una visión incompleta y sesgada del pasado, invisibilizando las contribuciones significativas de las mujeres. Esta falta de representación no solo afecta la memoria colectiva, sino que también perpetúa estereotipos de género y limita el reconocimiento del papel fundamental de las mujeres en la construcción de la sociedad orense. Para recuperar y visibilizar el legado de las mujeres orenses, se propone una metodología de investigación que combina la revisión de fuentes documentales –archivos, libros, fotografías– con la recuperación de testimonios orales –entrevistas a mujeres orenses y sus descendientes–. Además, se plantea la creación de una obra artística escultórica en metal que sirva como homenaje y reconocimiento a estas mujeres, difundiendo su legado de manera creativa y accesible. La obra escultórica referente a la mujer realizada en metal se concibe como una pieza artística que dialoga con la investigación histórica, representando simbólicamente la fuerza, la resiliencia y el legado de las mujeres orenses, A través de su forma, textura y materiales, la escultura busca transmitir la presencia y la importancia de estas mujeres en la historia de la región. Esta obra está compuesta por ocho piezas de metal, las cuales tienen diferentes tamaños que al juntarlas forman un rostro, este va hacer ilusión de los rostros de las mujeres que han hecho historia y no se tiene información de ellas, de igual manera en el tablero base donde se anclara la pieza tendrán diferentes contextos históricos pegados pero estos empezaran siendo grandes, visibles hasta que dé a poco estos mismos contextos van disminuyendo haciéndose cada vez más pequeños, dando a entender que así se ve este tema ante los ojos de la sociedad ya que se puede deducir que la mayoría de las personas, no tienen conocimiento de esta situación crítica que genera un espasmo informativo en la provincia del Oro. Se espera que esta obra se convierta en un espacio de encuentro y reflexión, invitando a la comunidad a reconocer y valorar el aporte de las mujeres en la construcción de su sociedad.
Keywords: HISTORIA; MUJER; ESCULTURA; REGISTRA; VISIBILIZAR